1992
DOI: 10.1111/j.1464-410x.1992.tb15571.x
|View full text |Cite
|
Sign up to set email alerts
|

Norfloxacin Prophylaxis for Endoscopic Urological Surgery

Abstract: A series of 140 patients, undergoing various types of urological endoscopic procedures, was divided into 2 equal, parallel, randomised groups. The first group of 70 patients, undergoing lower urinary tract surgery, was randomised, half to receive norfloxacin prophylaxis and half no antibiotic cover; the other 70 patients, undergoing percutaneous renal surgery, were randomised, half to receive norfloxacin and half cefuroxime. It was found that 26% of patients not receiving antibiotic prophylaxis and 11% on cefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The recommended antimicrobials to prevent UTIs after TUR-Bt are injective CEPs and oral fluoroquinolones (FQLs). [16][17][18][19][20]22,28,[30][31][32][33][34][35] Attention to fluoroquinolone-resistant Escherichia coli should be paid , however, because its prevalence has been reported. 36 In Western countries, the dosages of antimicrobials are higher than that in Japan.…”
Section: (2) Perioperative Infections In Tur-bt 13-20mentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended antimicrobials to prevent UTIs after TUR-Bt are injective CEPs and oral fluoroquinolones (FQLs). [16][17][18][19][20]22,28,[30][31][32][33][34][35] Attention to fluoroquinolone-resistant Escherichia coli should be paid , however, because its prevalence has been reported. 36 In Western countries, the dosages of antimicrobials are higher than that in Japan.…”
Section: (2) Perioperative Infections In Tur-bt 13-20mentioning
confidence: 99%
“…On the other hand , 3-day AMP has been recommended in some studies. 16,26 No past studies on the comparison between 1-day and 3-day administration are available. Furthermore, the catheter-indwelling time was not unified in all of the past studies.…”
Section: (2) Perioperative Infections In Tur-bt 13-20mentioning
confidence: 99%
“…The incidence (3.4%) was equivalent to that (2.3%) in patients with single dose of fluoroquinolone, which some previous studies recommended as AMP for TURBT. [1][2][3][4][5][6] Moreover, these symptomatic UTIs were easily treated by deferred use of antibiotics. Three of the four patients having UTIs with no AMP received only oral antibiotics, and the remaining one was treated by parenteral treatment for several days.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were a few studies to evaluate the efficacy of AMP on infectious complications after TURBT with controversial results. Some studies have recommended the use of AMP for TURBT [1][2][3][4][5][6][7][8][9] because of the relatively high incidences of postoperative urinary tract infections (UTIs) including bacteriuria ranging from 10% to 40%. 10,11 Other studies reported that AMP for TURBT is not necessary.…”
Section: Introductionmentioning
confidence: 99%
“… NRF is a widely applied antibiotic for the treatment of respiratory and urinary tract infections, as well as skin infections . In addition, NRF is a safe and effective prophylactic antibiotic used in all forms of urological endoscopic surgery and for minimizing the rate of catheter‐associated bacteriuria and pyuria that can occur after reconstructive gynaecologic surgery …”
Section: Introductionmentioning
confidence: 99%